The effect of growth regulators and water-soluble fertilizers on laboratory and field germination of large-fruited and nutmeg pumpkin seeds - N. B. Ryabchikova; D. S. Shaposhnikov; S. M. Nadezhdkin (Овощи России, 2023)
Relevance and methodology. This article presents the results of a study on the effect of growth regulators and water-soluble fertilizers on laboratory and field germination of pumpkin seeds of various types. The results of observations of the growth and development of seedlings and roots are presented. The research was carried out by laboratory and field experience. It is established that based on the analysis of the data obtained, it can be concluded that growth regulators have a significant effect on the laboratory and field germination of pumpkin seeds of various species. Treatment of pumpkin seeds with growth regulators and water-soluble fertilizers is one of the promising methods of preparation for sowing. Not only field germination depends on high-quality seeds, but also the density of standing plants, as well as growth, development and disease damage. The variety of active substances in the studied growth regulators have a positive effect on the embryo, activating the accelerated process of nutrient absorption, providing increased germination energy and seed growth strength. There are many requirements for seed material. Germination is the main sowing quality of seeds, it is the ability to give seedlings (in the laboratory) or (in the field) shoots for a certain period of time. Germination also depends on the conditions of storage and germination of seeds. Another important property is the germination energy, the seeds should sprout in a certain time. The higher the germination energy, the seeds are considered better.Results. The use of various types of growth regulators in the technology of pumpkin cultivation, as studies show, is one of the promising agrotechnical measures. The best result when soaking pumpkin seeds of large-fruited pumpkin, in laboratory conditions, was achieved in variants with the use of growth regulators Vigor Forte- 98% and Phytozont – 95%. When soaking nutmeg pumpkin seeds, the best option was also shown by Vigor Forte and Phytozont – 95%.